THE EFFECT OF HUMAN RESOURCE MANAGEMENT PRACTICES ON ORGANIZATIONAL INTELLIGENCE IN JORDANIAN COMMERCIAL BANKS - Dr. Fawzieh Mohammad Mas’ad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to identify the impact of Human Resource Management (HRM) practices on organizational intelligence in Jordanian commercial banks. In order to achieve the objective of the study, a questionnaire was prepared by the researcher and distributed to a random sample of (250) managers who work in Jordanian commercial banks located in Amman City. The number of questionnaires that are valid for analysis was (212) questionnaire. For the purposes of data analysis, the study relied on the Statistical Package for Social Sciences (SPSS).The results of this study indicated that there is an effect of HRM practices (recruitment and staffing, training, compensation and rewards, and performance appraisal) on organizational intelligence dimensions (sensing, and responding capabilities). The study recommended that banks’ managers need to continue developing appropriate HRM practices that enhance the capabilities of banks to sense and respond to different surrounding changes, as this has a positive impact on improving intelligence, profitability and success of these banks in the future.